Penegakan Hukum terhadap Geng Motor Anak di Kota Jambi: Hambatan dan Strategi Penanggulangannya - Sylvia Nabila; Walter Sinaga; Herli Antoni; Iwan Darmawan (Juris Prima: Jurnal Inovasi Hukum dan Kebijakan, 2026)
The existence of juvenile motorcycle gangs has emerged as a social and legal phenomenon causing public unrest in Jambi City. Minors, who should ideally be under the guidance of educational institutions and families, are increasingly entangled in street violence, thereby disrupting public order and escalating street crime rates. This study addresses three crucial issues: the effectiveness of law enforcement against juvenile motorcycle gang members in Jambi City, the obstacles encountered during the enforcement process, and the mitigation efforts implemented by law enforcement agencies to reduce these crimes. This study employs an empirical juridical method with a socio-legal approach, utilizing data gathered through field observations and interviews with local law enforcement officers. The findings indicate that current law enforcement faces a dilemma between imposing criminal sanctions and protecting children's rights under the Juvenile Criminal Justice System Act. Primary obstacles include systemic legal and enforcement factors, inadequate infrastructure, community apathy, and cultural misconceptions where social media-driven violence is perceived as a trend among adolescents. Mitigation efforts involve comprehensive strategies—comprising pre-emptive education, preventive actions, and repressive measures—that remain strictly oriented toward the best interests of the child. In conclusion, progressive law enforcement requires a balanced combination of firm repressive actions for serious offenses and preventive, community-based education to break the regenerative cycle of juvenile motorcycle gangs in Jambi City.